2003
DOI: 10.1099/jmm.0.05161-0
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of urine mineral components may depend on the chemical nature of Proteus endotoxin polysaccharides

Abstract: Formation of infectious urinary calculi is the most common complication accompanying urinary tract infections by members of the genus Proteus. The major factor involved in stone formation is the urease produced by these bacteria, which causes local supersaturation and crystallization of magnesium and calcium phosphates as carbonate apatite [Ca 10 (PO 4 ) 6 .CO 3 ] and struvite (MgNH 4 PO 4 .6H 2 O), respectively. This effect may also be enhanced by bacterial polysaccharides. Macromolecules of such kind contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 27 publications
2
55
0
1
Order By: Relevance
“…It was found that struvite exhibits polar properties , ROMANOWSKI et al 2010. TORZEWSKA et al (2003) confirmed this observations and showed that urinary stone formation due to the urease activity, may be modified by surface O-antigens being a part of lipopolysaccharides (LPS). The sugar composition of these polysaccharides may either enhance or inhibit the crystallization of struvite and carbone apatite depending on their chemical structure and ability to bind cations.…”
Section: Pathogenicitysupporting
confidence: 63%
“…It was found that struvite exhibits polar properties , ROMANOWSKI et al 2010. TORZEWSKA et al (2003) confirmed this observations and showed that urinary stone formation due to the urease activity, may be modified by surface O-antigens being a part of lipopolysaccharides (LPS). The sugar composition of these polysaccharides may either enhance or inhibit the crystallization of struvite and carbone apatite depending on their chemical structure and ability to bind cations.…”
Section: Pathogenicitysupporting
confidence: 63%
“…Additionally, this barrier plays a role in late biofilm development (346) and protects against desiccation and phage attack. It also assists in accelerating the urinary stone crystallization process via electrostatic interactions that accumulate urinary ions at the bacterial surface (55,87,408). During the course of UTIs, antibodies that recognize antigenic components of uropathogens are produced.…”
Section: Pathogenesis Of Cautismentioning
confidence: 99%
“…Due to the acidic, negatively charged residues on its surface, a possible function of LPS during UTIs and CAUTIs is its ability to attach and bind cations such as Ca 2ϩ and Mg 2ϩ , leading to the accumulation of these ions around bacterial cells and the acceleration of the crystallization process (408). Studies by Torzewska et al (408) indicated that the level of Ca 2ϩ and Mg 2ϩ cation binding on the surface of Proteus organisms is dependent upon the sugar composition of the Proteus LPS as determined by in vitro crystallization in artificial urine.…”
Section: Avoidance Of Host Immune Responsementioning
confidence: 99%
“…Both LPSs and CPSs have been considered to play an important role in the progression of UTIs, in addition to affecting both kidney and bladder stone formation (7,25,35). Furthermore, the LPS O antigen confers protection against serum-mediated bactericidal activity (13,27), and bacterial LPS released from bacteria is a biologically active endotoxin that causes a broad spectrum of pathophysiological conditions, including septic shock (26).…”
mentioning
confidence: 99%